A Comparative Analysis of Various Images in Bio Medical Using Artificial Neural Networks (International Journal of Engineering and Computer Science, 2017)
This paper Introduces a hybrid approach in selecting a best architecture of artificial neural networks to compare various medical images like lung segments, nodules, etc., Artificial neural networks are widely used for segmentation of tissues and structures from medical images. Through this study we can prove the effectiveness of the neuro Genetic approach in medical image segmentation. The proposed method minimizes training time and have increased the accuracy when compared to the existing method.